Web Application Design for the Control Process of Public Schools - Mendoza Santos, Carlos Daniel (2020)
The present research work was presented in the context of the deficit problematic in the inventory process of public school in Peru. The main objective is for public schools to use ICTs to improve this process. The methodology used for the development of the research work is Scrum, since it allows the application model to be carried out in an agile and organized manner. The different needs that each stage of the methodology presented were solved by the Balsamiq Mockups tool. In the results we can appreciate that implementing this web system offers speed and security to the management of the inventory of the public schools, since it is necessary to have a control of all the goods in real time. Therefore, this paper can be useful to public school functionaries who wish to implement a logistics system such as the one that has been designed